Fungicide sensitivity and spatial and temporal dynamics of Botrytis cinerea and Colletotrichum spp. in conventional and organic strawberry fields - Baggio, Juliana Silveira (2016)
Botrytis and Anthracnose fruit rots, caused by Botrytis cinerea and Colletotrichum spp., respectively, are major strawberry diseases. This study aimed to compare organic and conventional strawberry production systems by evaluating the sensitivity of B. cinerea and Colletotrichum spp. isolates to the main single-site fungicides used in Brazil and by characterizing the spatial and temporal dynamics of the diseases caused by these pathogens using epidemiological tools. Isolates were collected from conventional and organic fields in four different Brazilian states from 2013 to 2015. Resistance to azoxystrobin, iprodione and thiophanate-methyl was found in B. cinerea isolates with EC50 values higher than 71.9, 688 and 1.2 μg/ml, respectively. Resistance to the aforementioned fungicides was observed in 87.5, 76.6 and 92.2 % of isolates from conventional fields, and 31.4, 22.9 and 51.4 % of isolates from organic fields, respectively. Moreover, frequencies of populations with multiple fungicide resistance to the three active ingredients were 75 and 8.6 %, with no resistance to any of the fungicides were 6.25 and 34.3 % for isolates collected from conventional and organic areas, respectively. Molecular analyses of the cytochrome b, beta-tubulin and bos1 genes revealed, respectively, the presence of G143A, E198A and I365N/S, Q369P or N373S mutations in resistant populations of B. cinerea. Fungicides sprayed preventively on strawberry fruit inoculated with B. cinerea failed to control resistant isolates. Isolates of C. acutatum resistant to azoxystrobin and difenoconazole were not observed. Mean EC50 values for isolates collected from organic fields were 0.44 and 0.95 μg/ml, and from conventional areas were 0.629 and 0.107 μg/ml for azoxystrobin and difenoconazole, respectively. Populations of C. acutatum showed insensitivity to thiophanate-methyl rather than resistance and EC50 values could not be determined. None of the isolates contained the most common mutations associated with fungicide resistance. The temporal and spatial dynamics of Botrytis and Anthracnose fruit rots were characterized in the 2015 strawberry season in conventional and organic farms. Temporal progress models were fitted to the cumulative incidence of diseased strawberry fruit or plants over time with non-linear regressions. The spatial pattern of the diseases was analyzed according to the index of dispersion (D), the index of aggregation (V/M), and the Taylor\'s power law. The incidence-diseased fruit density relationship was analyzed by fitting a linear model. Fruit with symptoms of Colletotrichum spp. were not observed in the organic area and were found in few assessment dates in the conventional area. Incidence of Botrytis fruit rot in symptomatic fruit and plants were generally well described by the logistic model. The organic area presented disease incidence and daily progress rate higher than the conventional area. The aggregation of diseased fruit on strawberry plants were observed for both areas. Botrytis fruit rot presented similar epidemiological patterns for both conventional and organic areas, however, disease intensity was greater for the organic area; this was likely due to differences in disease control management. This study reinforces the importance for the implementation of integrated management programs in strawberry nurseries and production fields.